Case report: Vitiligo-like toxicity due to ribociclib during first-line treatment of metastatic breast cancer: two cases of premature interruption of therapy and exceptional response - Pasqualoni, Mariangela; Orlandi, Armando; Palazzo, Antonella; Garufi, Giovanna; Cannizzaro, Maria Chiara; Pontolillo, Letizia; Pannunzio, Sergio; Cutigni, Claudia; Sollena, Pietro; Federico, Francesco; Bria, Emilio; Tortora, Giampaolo (Frontiers in Oncology, 2023)
Cancer treatment-related adverse events (AEs) are sometimes associated with outcomes for cancer pa-tients, especially with the newest therapies such as target therapy and immunotherapy. A few years ago the first-line therapy for hormone-receptors-positive metastatic breast cancer (mBC) patients has been deeply changed by the introduction of cyclin-dependent kinase (CDK) 4/6 inhibitors and now we are improving our knowledge about their AEs and significance in clinical practice. Here we report our experience with two cases of vitiligo-like lesions that occur early on treat-ment with ribociclib. We tried to change the CDK4/6 inhibitor for one patient, but the skin reaction persisted. Both patients kept only the endocrine therapy alone and had an unexpected durable progres-sion-free survival (PFS). Some data on skin toxicities, including vitiligo-like lesions by CDK4/6 inhibitors, have been just reported in the literature but for the first time, we highlight a possible correlation with improved survival outcomes of patients. Uncovering the aetiology of this toxicity, verifying the involvement of the immune system and demonstrating a possible positive impact in survival, represent an intriguing research objective for the near future.